Gene network and canonical pathway analysis in canine myxomatous mitral valve disease: A microarray study. Issue 1 (April 2015) - Lu, C.-C.; Liu, M.-M.; Culshaw, G.; Clinton, M.; Argyle, D.J.; Corcoran, B.M.
Highlights: Microarrays were used to analyse transcript changes in canine myxomatous mitral valve disease (MMVD). In total, 591 differentially expressed genes were identified with 322 up-regulated and 269 down-regulated. Data suggest contribution of endothelial-to-mesenchymal transition to disease pathogenesis. Data will allow for hypothesis-driven research to understand MMVD. Abstract: Myxomatous mitral valve disease (MMVD) is the single most common acquired heart disease of the dog and is particularly common in small pedigree breed dogs such as the Cavalier King Charles spaniel (CKCS). There are limited data on the mitral valve transcriptome and the aim of this study was to use the microarray technology in conjunction with bioinformatics platforms to analyse transcript changes in MMVD in CKCS compared to normal dogs (non-CKCS). Differentially expressed genes ( n = 5397) were identified using cut-off settings of fold change, false discovery rate (FDR) and P < 0.05. In total, 4002 genes were annotated to a specific transcript in the Affymetrix canine database, and after further filtering, 591 annotated canine genes were identified: 322 (55%) were up-regulated and 269 (45%) were down-regulated. Canine microRNAs (cfa-miR; n = 59) were also identified. Gene ontology and network analysis platforms identified between six and 10 significantly different biological function clusters from which the following were selected as relevant to MMVD: inflammation, cell movement, cardiovascular development, extracellular matrix organisation and epithelial-to-mesenchymal (EMT) transition. Ingenuity Pathway Analysis identified three canonical pathways relevant to MMVD: caveolar-mediated endocytosis, remodelling of epithelial adherens junctions, and endothelin-1 signalling. Considering the biological relevance to MMVD, the gene families of importance with significant difference between groups included collagens, ADAMTS peptidases, proteoglycans, matrix metalloproteinases (MMPs) and their inhibitors, basement membrane components, cathepsin S, integrins, tight junction cell adhesion proteins, cadherins, other matrix-associated proteins, and members of the serotonin (5-HT)/transforming growth factor -β signalling pathway.